1999
DOI: 10.1017/s0272263199002028
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Vocabulary Acquisition in a Second Language

Abstract: It is widely agreed that much second language vocabulary learning occurs incidentally while the learner is engaged in extensive reading. After a decade of intensive research, however, the incidental learning of vocabulary is still not fully understood, and many questions remain unsettled. Key unresolved issues include the actual mechanism of incidental acquisition, the type and size of vocabulary needed for accurate guessing, the degree of exposure to a word needed for successful acquisition, the efficacy of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
211
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(243 citation statements)
references
References 41 publications
3
211
0
8
Order By: Relevance
“…therefore, encouraging learners to read and listen extensively can provide them with great opportunities and ample input the is necessary for vocabulary learning. According to Huckin and Coady (1999) except for the first few thousand most common words, L2 vocabulary learning predominantly happens through extensive reading with guessing of the unknown words. This process is incidental learning of vocabulary for the acquisition of new words and is the by-product of reading.…”
Section: A Incidental and Intentional Learning In L2 Vocabulary Litementioning
confidence: 99%
“…therefore, encouraging learners to read and listen extensively can provide them with great opportunities and ample input the is necessary for vocabulary learning. According to Huckin and Coady (1999) except for the first few thousand most common words, L2 vocabulary learning predominantly happens through extensive reading with guessing of the unknown words. This process is incidental learning of vocabulary for the acquisition of new words and is the by-product of reading.…”
Section: A Incidental and Intentional Learning In L2 Vocabulary Litementioning
confidence: 99%
“…Qian, 1996;File & Adams, 2010), using L1 and L2 in teaching vocabulary (e.g. Latsanyphone & Bouangeune, 2009;Webb, 2007), and teaching vocabulary through reading (e.g. Paribakht & Wesche, 1997;Sonbul & Schmitt, 2010).…”
Section: Vocabulary Learning In the Classroommentioning
confidence: 99%
“…Reading plays a key role in increasing learners' vocabulary, and that is according to comparisons of large corpora which showed that written texts are richer in lexis than spoken ones (Horst, 2005). It has been suggested that two activities (vocabulary learning and reading) occurring simultaneously create a 'pedagogically efficient' approach (Huckin & Coady, 1999), which could help learners achieve autonomy, motivation and pleasure to learn, while also providing them with vocabulary in context (Thornbury, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Huckin (1999), the simple extensive reading for meaning does not lead automatically to the acquisition of vocabulary. Since incidental acquisition is a complex psychological process, there are kinds of factors that can influence the effect of incidental vocabulary acquisition to different extent, such as the individual's English reading proficiency, the topic of reading materials, the frequency of the target words in reading, reading purposes, the vocabulary size, students' ability of guessing words, different reading tasks and different context, etc.…”
Section: Second Language Vocabulary Acquisition and Readingmentioning
confidence: 99%